Childhood Adversity and Pubertal Development Among Puerto Rican Boys and Girls. Issue 5 (June 2020) - Suglia, Shakira F.; Chen, Chen; Wang, Shuang; Cammack, Alison L.; April-Sanders, Ayana K.; McGlinchey, Eleanor L.; Kubo, Ai; Bird, Hector; Canino, Glorisa; Duarte, Cristiane S.
ABSTRACT: Objective: Evidence stemming largely from retrospective studies suggests that childhood adversity (CA) is associated with earlier age at menarche, a marker of pubertal timing, among girls. Little is known about associations with pubertal tempo among boys or racial/ethnic minorities. We examined the association between CA and timing and tempo of pubertal development among boys and girls. Methods: The Boricua Youth Study is a longitudinal study of Puerto Rican youth residing in the San Juan metro area in Puerto Rico and the South Bronx, New York. CA was based on caretaker reports of parental loss and parental maladjustment and youth reports of child maltreatment and exposure to violence. Youth completed the Pubertal Development Scale (PDS) yearly for 3 years. In linear mixed models stratified by sex, we examined the association between CA and pubertal timing and tempo, adjusting for site, socioeconomic status, and age. Results: Among the 1949 children who were 8 years or older by wave 3, cumulative CA was associated with higher PDS scores among girls compared with girls not exposed to CA (PDS score: 2.63 [95% confidence interval CI = 2.55–2.71] versus 2.48 [95% CI = 2.37–2.58]). In contrast, among boys, experiencing adversities was associated with lower pubertal developmental stage or later timing (PDS: 1.77 [95% CI = 1.67–1.87] versus 1.97 [95% CI = 1.85–2.10]) compared with those not exposed to adversities. Conclusions: Associations between CA and pubertal development may vary by sex. Understanding the etiological role of adversities on pubertal development and identifying targets for intervention are of utmost importance in ameliorating the impact of CA on child health. Abstract : Supplemental digital content is available in the text.